Early Growth Response Genes Signaling Supports Strong Paracrine Capability of Mesenchymal Stem Cells - Kenichi Tamama; Dominique J. Barbeau (Hindawi Limited, 2012)
MSCs provide a promising method for cell therapy through their wound healing and tissue regenerative properties. Originally, MSCs' role in wound healing was thought to be tied to their multipotency, but it is now accepted that MSCs mediate the healing process through their strong paracrine capability. EGF was shown to facilitate in vitro expansion of MSCs without altering multipotency. Our previous data suggest that the molecular machinery underlying MSCs' strong paracrine capability lies downstream of EGFR signaling, and we focus on transcription factors EGR1 and EGR2. Evidence suggests that EGR1 regulates angiogenic and fibrogenic factor production in MSCs, and an EGFR-EGR1-EGFR ligands autocrine loop is one of the underlying mechanisms supporting their strong paracrine machinery through EGR1. EGR2 appears to regulate the expression of immunomodulatory molecules. Chronic nonhealing wounds are ischemic, inflammatory, and often fibrotic, and the hypoxic micro-environment of these wounds may compromise MSCs' wound healing properties in vivo by upregulating the EGR1's fibrogenic effects and downregulating the EGR2's immuno-modulatory effects. Thus, these transcription factors can be potential targets in the optimization of cell-based therapies. Further study in vitro is required to understand MSCs' paracrine machinery and to optimize it as a tool for effective cell-based therapies.